Den tiende Forsamling af tydske Land- og Forstmænd, afholdt i Gratz i September 1840. - Hald, J. C. (Tidsskrift for Landøkonomi, 2018)
Den tiende Forsamling af tydske Land- og Forstmænd, afholdt i Gratz i September 1840.